Interdisciplinarity in Modern Science: Methodological Aspects - Vdovenko, Tetyana (Journal of Danubian Studies and Research, 2025)
Abstract: The article is devoted to methodologicalaspects of interdisciplinarityinmodernscience.Theessence of the interdisciplinaryapproach and itsdifferencefromrelatedforms of knowledgeintegration are considered. The historicalbackgroundandkeycharacteristics of interdisciplinaryresearch are analyzed.Specialattention is paid to methodologicalissues,includingterminologicalbarriers,differencesinstandardsandorganizationaldifficulties.Examples of successfulinterdisciplinaryprojectssuchasgenome sequencing andartificialintelligenceresearch are given.Theadvantages of interdisciplinarity,includinginnovativepotentialandintegratedsolutions to globalproblems, are discussed.There are alsochallengesrelatedto the academictraditionand the assessment of the quality of research. The articlehighlights the need to develop a methodologicalculture of interdisciplinarywork.